Minimização do risco de carteiras de investimento através da programação linear e da teoria de Markowitz - Freitas Junior, Carlos Moraes de (2022)
The study presented in this project aimed at the formation and optimization of portfolios with 20 shares traded on B3 based on Markowitz's modern portfolio theory and Linear Programming, considering the minimization of portfolio risk, modeled from a quadratic programming problem and solved through computationally implemented algorithm. The data collection period began in 2020, when there was a global economic crisis due to the COVID-19 pandemic and consequent isolation measures. Three portfolios were formed during the pandemic period, which were observed between January 2021 and March 2022 and showed results as expected compared to the 1/n strategy and the Ibovespa variation.